2013
DOI: 10.1142/s0219477513500168
|View full text |Cite
|
Sign up to set email alerts
|

Emg Amplitude Estimators Based on Probability Distribution for Muscle–computer Interface

Abstract: To develop an advanced muscle–computer interface (MCI) based on surface electromyography (EMG) signal, the amplitude estimations of muscle activities, i.e., root mean square (RMS) and mean absolute value (MAV) are widely used as a convenient and accurate input for a recognition system. Their classification performance is comparable to advanced and high computational time-scale methods, i.e., the wavelet transform. However, the signal-to-noise-ratio (SNR) performance of RMS and MAV depends on a probability dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…This performance was achieved by inputting the MAV feature of a Coif4 wavelet into a neural network of 20 hidden layers. This result is consistent with the conclusions reported in (Phinyomark et al, 2013) where it was shown that both MAV and RMS were accurate inputs for recognition and classification systems.…”
supporting
confidence: 93%
“…This performance was achieved by inputting the MAV feature of a Coif4 wavelet into a neural network of 20 hidden layers. This result is consistent with the conclusions reported in (Phinyomark et al, 2013) where it was shown that both MAV and RMS were accurate inputs for recognition and classification systems.…”
supporting
confidence: 93%
“…These are commonly employed features in myoelectric pattern recognition systems due to their high accuracy in low-noise environments and low computational complexity, and provide intuitive information about muscle motor unit recruitment [30,[52][53][54][55][56]. The mean absolute value (MAV) feature or root mean square (RMS) feature, for example, is a TD feature that represents the average energy of the EMG signal within a window [57,58]. FD features are extracted from the Fourier transform of the EMG signal to capture information about motor unit recruitment rates and muscle fatigue.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Mean and median frequency have been observed to increase [167,183,184], decrease [59,[185][186][187], or remain consistent as intensity increases. The probability distribution function of the EMG signal is typically described as a combination of Gaussian and Laplacian, with their weighting being dependent on the contraction intensity [58]. The distribution has been reported to tend towards towards Laplacian as intensity increases [188], Gaussian as intensity increases [189,190], or towards Laplacian as intensity deviates from 50% [191].…”
Section: Intensity Levelsmentioning
confidence: 99%
“…Following conventional EMG pattern recognition methods, the HD-sEMG map can be computed using the root mean square (RMS) [42] or other amplitude-based feature extraction methods (e.g., MAV, WL, etc.) [43], of individual channels distributed in 2D space. This map is thus also sometimes referred to as an intensity or heat map.…”
Section: High-density Surface Emgmentioning
confidence: 99%